Movement and Distribution of Ammonium-N Following Deep Placement of Urea in a Wetland Rice Soil - Savant, N.K.; De Datta, S.K. (Wiley, 1980)
The vertical distribution of NH4+‐N following subsurface placement of different forms of urea was studied in incubated, undisturbed wetland soil cores. For prilled urea, supergranule urea, and prilled urea in mudballs placed at the 10‐cm depth, peak concentration of NH4+‐N was near the placement site and decreased with time, whereas after placement of sulfurcoated urea (SCU‐21) at the same depth, peak concentration of NH4+‐N increased over a period of 4 weeks. With time, the NH4+‐N tended to move downward more than upward from the placement sites, probably because of the mass flow of percolating water.In another experiment, the movement and spatial distribution of NH4+‐N were studied following application of 2‐g supergranules of urea (SGU) and sulfur‐coated supergranules of urea (SC‐SGU) at a depth of 10 cm in transplanted and cultivated wetland fallow plots. After 2 weeks, NH4+‐N concentration gradient for SGU was 1,850 to 32 µg N/cm3 wet soil, over a distance of 10–12 cm from the placement site. The corresponding gradient for SC‐SGU was 287 to 32 µg N/cm3 wet soil, over a distance of 5–7 cm from its placement site. For SGU in transplanted plots, the concentration gradient decreased steadily through 8 weeks, whereas for SC‐SGU it increased during the first 4 weeks and then decreased. The disappearance of NH4+‐N with time and distance from the site of application is attributed to diffusive transport or convective transport, or both, and root‐sink effect. The general movement of NH4+‐N was downward > lateral > upward. The apparent benefits of deep placement of urea in a wetland rice soil are discussed.